Kyrgyz Republic : Review of Social Policy and Expenditures, Volume 1. Overview of Health, Education and Social Protection Issues - World Bank (Washington, DC, 2013)
In the first half of 1999, Kyrgyz authorities agreed with the International Development Association (IDA) that a review of Kyrgyz social expenditures, giving particular emphasis to health and education expenditures, would be valuable. This report presents findings from the resulting review undertaken between October 1999 and June 2000. The review team looked not only at these expenditures (including social protection) themselves, but also at their efficiency and effectiveness as a means for achieving Kyrgyz objectives in the social policy arena. The review team first examined medium-term priorities for social policy under sharp resource constraints, then considered feasible strategies for achieving these priorities, and finally looked at their implications for policies, administration, and public expenditures. The report is in 2 volumes. Volume 1 provides an overview of the findings on health, education, and social protection. Volume 2 offers more detailed critiques of expenditures and policies on health and education.